Cartographic representation of population indicators in the sustainable development goals in Iraq and analysis of the best methods - Al-Khilani, Bashar Amer Abdul Qadir; Al-Akedi, Wissam Ahmed Rashid (Al-Adab Journal, 2022)
This study came in accordance with the specialization of maps to discuss population indicators in the sustainable development goals in Iraq, with the exception of the governorates of the Kurdistan region (Sulaymaniyah, Erbil, Dohuk), where the study relied on the descriptive and analytical approach by collecting data and information obtained from libraries and government departments. The study showed a rise in unemployment rates in Iraq, reaching the highest rate (19.58%) in Anbar Governorate. The study also showed a high percentage of individuals using the Internet in Iraq for the year 2019, reaching the highest percentage (64.4%) in Baghdad Governorate, and the study confirmed that Existence of child labor (5-17 years) in Iraq for the year 2018. The study stressed the need to adopt investment projects aimed at reducing unemployment rates, developing the skills and capabilities of the productive group of young people, and providing job opportunities, with the importance of cultural awareness programs that limit the phenomenon of child marriage and raise the educational level.